Development of a multiscale electromechanical computer model from cell to hemodynamics. (24th May 2021) - Lyon, A; Arts, T; Delhaas, T; Lumens, J; Van Veen, AAB
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): CVON eDETECT 2015-12 Background: Patients with genetic cardiomyopathies mostly remain asymptomatic until the occurrence of life-threatening arrhythmias and sudden cardiac death. The responsible pro-arrhythmic mechanisms, as well as the indicators for pro-arrhythmia, often remain unclear. Current research approaches are commonly based on experimental animal models or clinical data obtained from mutation carriers. The translation (and bridging) of results obtained from experimental models to humans and scale integration of these findings remains challenging. As a consequence, clinical relevance is often disputed. In light of these challenges, computer modelling shows strong potential for its ability to capture the complex dynamics of the cardiovascular system across different scales. Purpose: We therefore aim to develop a multiscale electromechanical computer model coupling electrophysiology, sarcomere dynamics (contractility), whole-heart function and hemodynamics to investigate mechanisms (resulting from genetic predisposition to cardiomyopathy) of arrhythmogenicity and cardiac dysfunction in these patients. Methods: We coupled our previously published model of cellular electromechanics to the CircAdapt computer model of the heart and circulation. Electromechanical coupling was performed through the amount of calcium bound to troponin (as described in the cellular model). The same electrophysiological properties were assumed in all cardiac walls. Diffusion of calcium from the sarcolemmal space to the membrane was described phenomenologically through a resistance model. Results: Simulated hemodynamics properties were in range with control values with LVEDV = 110.8mL, LVESV = 38.7mL, RVEDV = 99.2mL, mLAP = 10.2mmHg, mRAP = 4.0mmHg. At the cellular level, sarcolemmal calcium transients showed the effect of mechanical change as illustrated by the bump in CaT. This effect was attenuated at the membrane due to the effect of diffusion. Alterations in the functionality of molecular entities underlying calcium homeostasis recapitulated cellular experimental findings as expected illustrated by implementing changes in adrenergic signaling. Conclusions: We have established a new multiscale electromechanical computer model describing electrophysiology, sarcomere mechanics and hemodynamics. The model simulates normal values in the control situation. Current work focusses on parameter sensitivity analysis and validation. Feeding this new model with experimentally obtained data from patient-specific models (ranging from individual cells to e.g. transgenic mouse models based on relevant mutations) therefore has potential to bridge the gap between pathogenic experimental models and patient data. This will add to the understanding of underlying mechanisms responsible for disease onset and progression, and furthermore could develop into a tool to identify patients/mutation carriers at risk for severe disease outcome.